Well-behaved 4H-SiC PMOSFET with LOCal oxidation of SiC (LOCOSiC) isolation structure and compromised gate oxide for Sub-10V SiC CMOS application. (April 2020) - Hung, Chia-Lung; Tsui, Bing-Yue
Highlights: A well-behaved 4H-SiC PMOSFET device with LOCOSiC isolation structure. SiC CMOS integrated circuit application. SiC PMOSFET device behavior and temperature response. High temperature environment and power electronics application. Abstract: SiC devices are suitable for high temperature applications due to its' wide energy bandgap and high thermal conductivity. Some SiC CMOSFET ICs have been reported recently. However, less literature address the characteristics of SiC PMOSFET. In this work, we fabricated PMOSFET with Local Oxidation of SiC (LOCOSiC) isolation structure and different gate oxidation processes targeting sub-10V operation. Well behaved PMOSFET with suitable threshold voltage (−5.58 V), low subthreshold swing (200 mV/decade), acceptable hole mobility (3 cm 2 /V-sec), and low off-state current (<1 × 10 −12  A/μm at −10 V) is achieved. Temperature dependence of device characteristics are investigated. These results make the implementation of high-performance CMOS a great progress.